Analisis Kinerja Openflow Based Switch pada Router Linkysys WRT54GL dan TP-Link TL-WR1043ND Dalam Arsitektur Software Defined Networking - Yasin Rizqi Afandi; Sabriansyah Rizqika Akbar; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In software defined network architecture (SDN) there is an open source protocol called Openflow. Openflow can be added to the open interface device. The Linkysys WRT54GL and TP-Link TL-WR1043ND routers can use Openflow by installing open-source firmware such as Openwrt. Several previous studies have tested the performance of LInkysys WRT54GL and TP-Link TL-WR1043ND routers based on network resource parameters such as throughput, round trip time and jitter. This study is conducted testing the performance of the Openflow protocol on the SDN architecture with adding parameters of computational. Computational parameters include the use of CPU and memory resources then, network parameters include round trip time, throughput and flow table formation time. Based on all test results, the addition of Openflow on the Linkysys WRT54GL and TP-Link TL-WR1043ND router who installed openwrt, can increase the use of CPU and memory resources and can degrade network performance such as round trip time and throughput. The decrease performance of router is due to the addition of the Openflow process on the router who cause decreased the switching performance and the mechanism of the Openflow hybrid switch who cause increased forwarding data processing time .